Harnessing macroalgae for heavy metal phytoremediation: A sustainable approach to aquatic pollution control - Ali Akbar Said; Nur Lestari Aisyah; Rizki Fazli Rahmad; Gunawan Gunawan (BIO Web of Conferences)
This review explores the potential of macroalgae in heavy metal phytoremediation, focusing on their ability to absorb and sequester toxic metals from contaminated aquatic environments. Heavy metals, pose significant ecological and health risks due to their persistence and bioaccumulation. Phytoremediation, particularly using macroalgae, offers a sustainable, eco-friendly alternative to traditional chemical methods. Data from various studies show that macroalgae species such as Sargassum wightii, Caulerpa racemosa, and Durvillaea antarctica demonstrate high efficiency in removing heavy metals. The review discusses key challenges such as scaling up macroalgae cultivation and the safe disposal of metal- laden biomass. Additionally, it highlights gaps in current research, emphasizing the need for standardized protocols and further investigation into the mechanisms of metal uptake. Overall, macroalgae-based phytoremediation presents a promising solution for mitigating aquatic pollution and enhancing ecosystem health.